Privacy, privatization, and the politics of patronage: ethnographic challenges to penetrating the secret world of Middle Eastern, hospital-based in vitro fertilization - Inhorn, Marcia C. (Social science & medicine (1982), 2004)
In recent years, in vitro fertilization (IVF) has spread around the globe, including to the Middle East. Privacy, privatization, and the politics of patronage are all key issues affecting anthropological research in Middle Eastern hospital-based IVF clinics. IVF-seeking patients generally desire privacy, even total secrecy, when pursuing these treatments, due to cultural issues of stigmatization, particularly regarding male infertility. Thus, ethical issues surrounding the informed consent process are of prime importance. Furthermore, privatization of medical services in the Middle East has left patients—and anthropologists—with few choices other than private IVF clinic settings in which to pursue treatment and research. Both the ethos of patient privacy and medical privatization affect the ability of anthropologists to “penetrate” the secret world of IVF. Permission to conduct ethnography in private hospital IVF clinics may be difficult to obtain without the help of highly motivated physician patrons, who are willing to recruit their private IVF patients for ethnographic interviewing. This article provides a personal account of some of these challenges as faced by a medical anthropologist during a 15-year career of hospital-based IVF research in the Middle East.